The Concept of Solidarity: Energy Policy in the European Union - Bartenstein, Aline (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Solidarity is a fuzzy concept although it is a core concept of the EU historically. Aline Bartenstein's book contributes to the clarification and analysis of the concept of solidarity between EU member states. In the theoretical part, she develops a novel conceptual approach to studying solidarity that goes beyond it having a purely political declarative function and is able to capture the dynamic of solidarity as a legal norm. In the empirical part, the author applies the concept to the integration processes in the natural gas sector between 2002 and 2019. Her analysis shows that an institutionalised principle of solidarity is in the making in the EU.